The Microcontroller Based Earthquake Detection and Magnitude Measuring (Richter Scale) System for Risk Mitigation - Bakti, Ilham Dwi; Ferdian, Rian (Universitas Andalas, 2025)
Earthquakes are unpredictable disasters that can cause immediate structural collapse, posing significant risks, especially when occurring at night or early morning when people are asleep and slower to react. To mitigate these risks, this research aims to design a microcontroller- based system for detecting earthquakes and measuring their magnitude using Richter scale. The system employs an SW420 sensor to detect tremors and an ADXL345 accelerometer to detect and measure acceleration of eartquakes, which is then converted into magnitude using formula. The system is equipped with an alarm that activates if magnitude exceeds 5.0 SR and PIR HC-SR501 sensor to detect the user’s presence. Additionally, it can activate a 5-watt emergency light and use a GSM SIM800L module to send SMS notifications and make calls to the User’s nearest contacts in the event of a significant earthquake. The research methodology involves Action Research, which includes reflection, action, and continuous adjustment. The findings indicate that system can detect vibrations up to 60 cm away and measure earthquake magnitudes starting from 1.0 SR. The alarm successfully activates for magnitudes greater than 5.0 SR, and system can detect the user’s existence presence up to 250 cm in both dark and light conditions. Furthermore, system effectively activates the emergency light and send SMS notification and nall if the magnitude exceeds 5.0 SR. This research confirms that the system performs as intended, helping to mitigate earthquake risks and providing crucial information to user.